PERTUMBUHAN USAHA PERSPEKTIF KREDIBILITAS PEMBIAYAAN EKSTERNAL PADA KOPERASI-KOPERASI DI PANGANDARAN - Muhyi, Herwan Abdul; Sukoco, Iwan (Program Studi Keuangan & Perbankan, Fakultas Ekonomi dan Bisnis, Universitas Komputer Indonesia, 2017)
Business growth is a process to business success. Cooperative as a business entity in the form of business entity, has a good growth indicator of profitability aspect size organization, the amount of human resources, asset growth, credibility in the eyes of finance institutions and others. This study aims to describe the growth of cooperatives from the point of view of the credibility of financing from external financing. This research uses descriptive analysis. The condition of external financing credibility is described from the results of a survey of 34 cooperative management representatives in Pangandaran Regency. Interviews were conducted on cooperative management and Section Head of Protection and Empowerment of Cooperatives in Pangandaran Regency. The results showed that the level of trust of external financing to cooperatives in Pangandaran Regency is 38.82%. This shows that the trust of external parties in providing capital loans is still lacking. Keywords: Business Growth, External Financing Credibility